2022
DOI: 10.30773/pi.2022.0142
|View full text |Cite
|
Sign up to set email alerts
|

Parental Psychological Aggression and Phubbing in Adolescents: A Moderated Mediation Model

Abstract: Objective The present study aimed to examine the mediated moderation effect underlying the association between parental psychological aggression and phubbing, as well as the mediating role of anxiety and moderating role of sex and grade.Methods Based on a cross-sectional study, a total of 758 Chinese junior high school students had completed measures on socio-demographic characteristics, parental psychological aggression, anxiety and phubbing. Structural equation modeling was adopted to examine the mediating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Pitifully, most previous studies on phubbing mainly focused on its adverse consequences, while only limited research has revealed the potential determinants (Garrido et al, 2021). The previous studies concerning antecedents of phubbing reveal that boredom (Doumit et al, 2023;Lv & Wang, 2023), depression (Sun & Samp, 2021), narcissism (Akat et al,2022;Grieve & March, 2020), parental psychological aggression (Gao et al, 2022), and parental phubbing (Liu et al, 2022) can predict phubbing positively, while open-mindedness (Doumit et al, 2023) and agreeableness (Sun & Samp, 2021) can predict phubbing negatively. However, an important risk factor, social anxiety, has been largely ignored from previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Pitifully, most previous studies on phubbing mainly focused on its adverse consequences, while only limited research has revealed the potential determinants (Garrido et al, 2021). The previous studies concerning antecedents of phubbing reveal that boredom (Doumit et al, 2023;Lv & Wang, 2023), depression (Sun & Samp, 2021), narcissism (Akat et al,2022;Grieve & March, 2020), parental psychological aggression (Gao et al, 2022), and parental phubbing (Liu et al, 2022) can predict phubbing positively, while open-mindedness (Doumit et al, 2023) and agreeableness (Sun & Samp, 2021) can predict phubbing negatively. However, an important risk factor, social anxiety, has been largely ignored from previous studies.…”
Section: Introductionmentioning
confidence: 99%